Air-Core Sensors Operation Modes for Partial Discharge Detection and On-line Diagnostics in Medium Voltage Networks - Kütt, Lauri; Shafiq, Muhammad; Lehtonen, Matti; Mõlder, Heigo; Järvik, Jaan (Electrical, Control and Communication Engineering, 2013)
In this paper, sensors for the application of high voltage networks insulation diagnostics are focused on. For detection and localization of the components with insulation deterioration, observing the partial discharge transients is one of the main methods. However, as the partial discharge traces are transients of extremely short duration, monitoring of such transients is also a challenging task. This paper presents the inductive sensors that would be suitable for the on-line partial discharge monitoring and the selection of operating mode and characteristics are discussed. The issues of resonance and signal processing are analyzed for the targets of reaching highest accuracy of the measurements. Operation criteria and performance limits such as sensitivity and upper bandwidth are particularly discussed. It is presented that in order to reach highest accuracy and sensitivity the sensor should be used in damped mode. Applying the accurate air-core inductive sensors would allow the condition monitoring systems to be cheaper and thus mounted for permanent and continuous condition monitoring in various locations in the power distribution networks.